Considerations on the site-specific concept in Brazilian Theatre - Silva, José Jackson (2020)
In this article we visit a set of definitions about the use of the term site-specific in contemporary Brazilian theater productions. For this purpose, we start from various definitions starting with the allusion that the visual arts make to expression. We seek to problematize the aspects of the creative process considering the word of creative agents, when expressing themselves in the programs of their shows or in interviews, the expression of specialized criticism and academic and university texts that seek to address the most different aspects involving the term and notion that encloses it.